2010
DOI: 10.1227/01.neu.0000370603.45342.6b
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Restoration in Cortical Level After a Contralateral C7 Nerve Transfer to an Injured Arm in Rats

Abstract: The cortical reorganization occurred only in the ipsilateral hemisphere, which is different from the motor cortex reorganization using the same model as that described in a previous study. This reorganization pattern offers an interpretation of the unique sensory recovery process after the transfer of the C7 nerve to the contralateral median nerve, but also provides the basis for further sensory restoration in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
12
2
Order By: Relevance
“…The findings during right median nerve stimulation are in contrast to the results of Wang et al 11 for sensory reorganization after contralateral C7 nerve transfer. In their study, they measured cortical activation by direct cortical stimulation of somatosensory evoked potentials and failed to find transhemispheric cortical reorganization in S1FL.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings during right median nerve stimulation are in contrast to the results of Wang et al 11 for sensory reorganization after contralateral C7 nerve transfer. In their study, they measured cortical activation by direct cortical stimulation of somatosensory evoked potentials and failed to find transhemispheric cortical reorganization in S1FL.…”
Section: Discussioncontrasting
confidence: 99%
“…9,10 Whereas some authors have investigated cortical changes that take place in response to the contralateral C7 nerve transfer procedure, these studies have relied on invasive testing, few time points, or no controls. 1114 …”
Section: Introductionmentioning
confidence: 99%
“…Task-based functional imaging studies showed intra- and inter-hemispheric cortical plasticity in rats and humans following contralateral C7 nerve transfer for BPAI [6–10]. However, task-based fMRI scan is challenging for most BPAI patients who have to accomplish motor function of the affected wrist and fingers by bilateral associated movements, which result in movement artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The unique clinical phenomenon suggests extensive cortical reorganization in the bilateral motor cortex. However, the central mechanisms underlying motor plasticity after contralateral C7 nerve transfer remain unclear, although a few functional imaging studies showed intra-hemispheric and inter-hemispheric cortical plasticity in rats and humans [6–10]. However, the interactions of motor networks in the resting state after contralateral C7 nerve transfer have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia and whole root avulsion of the left brachial plexus were identical to the procedure described earlier [13]. Briefly, each rat was anesthetized by an intraperitoneal injection of sodium pentobarbital (40-50 mg/kg; Shanghai Reagent Company, Shanghai, China).…”
Section: Brachial Plexus Avulsion Operationmentioning
confidence: 99%